The Influence of Promotion, Price and Brand Image on Purchasing Decisions: Study of Homedoki Furniture Store Consumers in Tangerang - Osi Ayudia; Rina Ayu Vildayanti (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this research is to determine the influence of promotion, price and brand image on purchasing decisions for the Homedoki Furniture Store in Tangerang. This research uses a Non Probability Sampling technique using a saturated sample method. The population in this study was 35 respondents. This research was carried out using the multiple linear regression method assisted by the SPSS version 25 program and Microsoft Excel 2013. The results of the research used the Multiple Linear Regression Analysis Method Y = 1.166 + 0.474 (X1) + - 0.152 (X2) + 0.656 (X3) + € , so it can be concluded that Promotion has a significant effect on Purchasing Decisions, Price has no effect on Purchasing Decisions, and Brand Image has a significant effect on Purchasing Decisions.